2018
DOI: 10.1146/annurev-arplant-042817-040431
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Recombination: Mixing It Up in Plants

Abstract: Meiosis halves diploid chromosome numbers to haploid levels that are essential for sexual reproduction in most eukaryotes. Meiotic recombination ensures the formation of bivalents between homologous chromosomes (homologs) and their subsequent proper segregation. It also results in genetic diversity among progeny that influences evolutionary responses to selection. Moreover, crop breeding depends upon the action of meiotic recombination to rearrange elite traits between parental chromosomes. An understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
234
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(239 citation statements)
references
References 259 publications
4
234
1
Order By: Relevance
“…This bias in the distribution of recombination events is particularly pronounced in the large grass family (Poaceae), including cereal crops (Higgins et al , 2014). Meiotic function is evolutionarily well conserved even though the amino acid sequences of recombination and particularly SC proteins are variable in different species (Grishaeva and Bogdanov, 2017; Wang and Copenhaver, 2018). Phylogenomic, mutagenic, and immuno-cytological tools have been extensively used to clone and characterise plant orthologues of meiotic genes (Lambing et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This bias in the distribution of recombination events is particularly pronounced in the large grass family (Poaceae), including cereal crops (Higgins et al , 2014). Meiotic function is evolutionarily well conserved even though the amino acid sequences of recombination and particularly SC proteins are variable in different species (Grishaeva and Bogdanov, 2017; Wang and Copenhaver, 2018). Phylogenomic, mutagenic, and immuno-cytological tools have been extensively used to clone and characterise plant orthologues of meiotic genes (Lambing et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate separation of chromosomes depends on the successful completion of homologous recombination and formation of meiotic crossovers (COs). COs establish physical links between homologs, which play a vital role in balancing the opposite pulling force of the spindle at metaphase I (Wang and Copenhaver, 2018).…”
mentioning
confidence: 99%
“…In budding yeast (Saccharomyces cerevisiae), synaptonemal complex (SC) assembly and interference-sensitive CO formation rely on a group of functionally related proteins consisting of molecular zipper 1 (ZIP1), ZIP2, ZIP3, ZIP4, MutS homologue 4 (MSH4), MSH5, meiotic recombination 3, and sporulation 16 (SPO16; ZMM proteins; Lynn et al, 2007;Shinohara et al, 2008). It has been demonstrated that ZMM orthologs are evolutionarily conserved in many other eukaryotes, including the model plants Arabidopsis (Arabidopsis thaliana) and rice (Oryza sativa; Wang and Copenhaver, 2018). ZIP1 encodes the transverse filament protein of the SC.…”
mentioning
confidence: 99%
“…At least two pathways (Type I and Type II), contribute to CO formation 2,3 . The Type I pathway leads to interfering COs that prevent the coincident occurrence of closely spaced CO on the same pair of chromosomes 2,8,9 .…”
Section: Mainmentioning
confidence: 99%